Glucosides from the Fresh Flowers of Juglans regia L. and Their Biological Evaluation - Wang, Haibo; Liu, Xikui (Letters in Organic Chemistry, 2020)
The chemical investigation of the EtOAc extract of the fresh flowers of Juglans regia L. resulted in a new α-tetralonyl glucoside (1) and two known glucosides (2-3). The structure of the new compound was determined by extensive 1D and 2D NMR spectroscopic analysis and HRESIMS. The biological evaluation of the obtained glucosides showed that compound 1 and 3 displayed good antioxidant and antibacterial activities. These two compounds were identified as the main functional molecules in the fresh flowers of Juglans regia L.
Keywords: juglandaceae